Comparing the diagnostic accuracy of semi-rigid and rigid pleuroscopy in diagnosis of exudative lymphocyte dominant pleural effusion with - Hamid Borsi; Mohammad Reza Farahnak; Hanieh Raji; Maryam Haddadzadeh Shooshtari; Behnam Pirhayati (Journal of Family Medicine and Primary Care, 2020)
Background and Objectives: Pleuroscopy is an appropriate technique for visualization and biopsy of the pleural lesions, performed by two different techniques. In this study, we aimed to investigate the diagnostic accuracy of semi-rigid and rigid pleuroscopy in patients with lymphocyte dominant exudative pleural effusion. Materials and Methods: In this study, patients with lymphocyte dominant pleural effusion with negative results for tuberculosis who referred to Imam Khomeini Hospital, Ahvaz, Iran; from 2018 to 2019 were selected by census method and randomized to undergo semi-rigid or rigid pleuroscopy (30 in each group). Patients' demographic, such as age and gender, were recorded and the pathologic results reported by the two pleuroscopy methods were compared and sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were reported for each method. All statistical analyses were performed using SPSS v. 21. Results: Thirty patients were included in each group. The frequency of tuberculosis, malignancy, and other causes of pleural effusion had no difference between the two methods (P > 0.05). Semirigid pleuroscopy had a sensitivity of 81.5%, specificity of 66.6%, PPV of 75.6%, and NPV of 74%, while the relevant values in rigid pleuroscopy were 87.2%, 68.4%, 87.2%, and 68.4%, respectively. Conclusion: These results, consistent with previous studies, indicated that both semi-rigid and semi-flexible pleuroscopy methods are accurate for diagnosis of lymphocyte dominant pleural effusion when performed by skilled specialists and other considerations, such as availability and costs, can be used for selection of each method.